EDUCATION IN THE FIVE MALAY PROVINCES: SINGAPORE MALAYSIA BRUNEI PHILIPPINES AND THAILAND - Mustakim; Faridi; Kamaludin, Moh. (As-Sulthan Journal of Education, 2025)
This study examines the development of educational systems in five regions of the Malay World, namely Singapore, Malaysia, Brunei Darussalam, the Philippines, and Thailand, with a focus on the relationship between education, religion, culture, and colonial influence. The purpose of this study is to analyze the characteristics, similarities, and differences of educational systems in each region and their role in preserving cultural and religious identity. This research employs a descriptive qualitative approach using a literature review and historical analysis of relevant sources. The findings reveal that each region’s educational system has evolved through different historical dynamics. Singapore emphasizes technological modernization supported by a bilingual education policy. Malaysia has developed an inclusive national education system while strengthening Islamic education through pondok and national schools. Brunei Darussalam places Islamic education at the core of its national curriculum through the philosophy of Malay Islamic Monarchy. The Philippines shows a dual system between secular education and Islamic madrasah in Mindanao. Meanwhile, Thailand maintains the dominance of Buddhist-based education alongside the existence of pondok and madrasah in the southern region. This study concludes that educational modernization in the Malay World continues to progress without abandoning traditional and religious values.